BIO-CHEMICAL MILIEU OF BUFFALOES OVARIAN FOLLICLES DURING THEIR DEVELOPMENT - LONE, A M; GUPTA, H P; PRASAD, SHIV; BAITHALU, R K (The Indian Journal of Animal Reproduction, 2023)
Biochemical constituents of ovarian follicular fluid were studied in relation to size of follicle in buffaloes. In the present study, ovaries were collected immediately after slaughter and the follicular fluid was aspirated and stored at-20°C. Sampling was done and were analysed for various biochemical constituents. Small follicle had significantly lower (P<0.05) concentrations of glucose, cholesterol, oestradiol, progesterone and sodium, while as the concentration of alkaline and acid phosphatase and potassium was significantly (P<0.05) higher.